The driving effect of the retail market system on the evolution of agricultural planting structure under price transmission: a structural equation model based on the interval number expansion algorithm - Liu, Kan; Sun, Xueying; Jin, Xin; Zhou, Hongrui (Frontiers in Sustainable Food Systems, 2025)
At present, accelerating the transformation of China’s traditional agricultural industry into modern agriculture and upgrading the agricultural planting structure from a low-value chain to a high-value chain is of utmost importance. Exploring the relationship between the retail market system and the price and scale of agricultural product has critical practical significance and long-term value for precisely guiding and effectively promoting the optimization and upgrading of the agricultural industry structure. Based on the analysis of the impact mechanism of the retail market on the agricultural planting structure through the price transmission mechanism, this study collected relevant data from 31 provinces over the past 10 years. Using the interval number expansion DEMATEL method and differential evolution algorithm, a structural equation model was constructed to study how the retail market system influences the agricultural planting structure through the mediating role of price transmission. The results show that the retail market has a primarily negative impact on prices, a significant positive impact on the agricultural planting structure, and that price plays an evident mediating role between the retail market and the agricultural planting structure. Based on the empirical results, this paper suggests that the government should formulate targeted policies according to market characteristics during the initial, developmental, and rapid transformation stages of the retail market to guide the transformation and upgrading of the agricultural planting structure in each province.